Plans and drawings by Leopoldo Torres Balbás in archival holdings: analysis and interpretation - Vincenzina La Spina; Pedro Miguel Jimenez Vicario (Disegnare con)
The important legacy of the architect Leopoldo Torres Balbás (Madrid, 1888-1960) has been extensively studied in all the fields in which he excelled. However, according to his own words, expressed in an article signed under a pseudonym in 1920, he lacked skills as a draftsman. Whether this claim is true or not, understanding how Torres Balbás approached drawing, identifying his assistants and collaborators, and examining what distinguishes the plans created under his guidance and what he drew, are the key objectives of this article. These will help us explore his role as a draftsman through an analysis of the archival materials that have been preserved. They are distributed among various Spanish archives, which hold original documents by or belonging to Torres Balbás. However, their authorship is not always clearly indicated, as with some of the graphic materials accompanying his publications, which make up a bibliography of over 300 scientific works. Therefore, methodologically, after searching for documentary sources, selecting the principal graphic documents, and comparing them with the drawings illustrating his articles, it has been possible to determine their author¬ship and subsequently analyse and systematise the vast graphic material preserved by the architect. Finally, the research carried out has been possible, first, to gain a deeper understanding of Torres Balbás’s figure and his real skills in graphic matters; second, to identify the key figures that helped and collaborated with him: draftsmen, architects, students, etc.; and third, to uncover his actual relationship with drawing. DOI: https://doi.org/10.20365/disegnarecon.34.2025.20